2002
DOI: 10.1016/s1053-8100(02)00026-0
|View full text |Cite
|
Sign up to set email alerts
|

Influences of visibility, intentions, and probability in a peripheral cuing task

Abstract: According to the concept of direct parameter specification, nonconsciously registered information can be processed to the extent that it matches currently active intentions of a person. This prediction was tested and confirmed in the current study. Masked visual information provided by peripheral cues led to reaction time (RT) effects only if the information specified one of the required responses (Experiments 1 and 3). Information delivered by the same masked cues that did not match the intentions was not use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 25 publications
5
44
0
2
Order By: Relevance
“…Of note, this was true even for free-choice blocks that immediately followed mixed blocks: No carryover effects from the previously relevant arrows were observed when participants were not explicitly instructed to respond to arrows . Corresponding results have been obtained in a number of different motor priming tasks employing the metacontrast paradigm (e.g., Ansorge et al, 2002;Klotz & Neumann, 1999;Kunde et al, 2003), suggesting that the instruction dependency of subliminal motor priming effects is not paradigm specific but reflects a fundamental feature of the underlying perceptuo-motor control processes.…”
supporting
confidence: 55%
“…Of note, this was true even for free-choice blocks that immediately followed mixed blocks: No carryover effects from the previously relevant arrows were observed when participants were not explicitly instructed to respond to arrows . Corresponding results have been obtained in a number of different motor priming tasks employing the metacontrast paradigm (e.g., Ansorge et al, 2002;Klotz & Neumann, 1999;Kunde et al, 2003), suggesting that the instruction dependency of subliminal motor priming effects is not paradigm specific but reflects a fundamental feature of the underlying perceptuo-motor control processes.…”
supporting
confidence: 55%
“…For example, if a conflict-eliciting condition with a masked and therefore invisible word plus a visible target word (e.g., a girl's name as a prime preceding a boy's name as a target) is so probable in the context of an experiment that participants would be well advised to prepare for an alternative response (e.g., prepare pressing the key for boy's name when the prime is a girl's name) than the one that would be indicated by the invisible prime word (e.g., the key for a girl's name when the prime is a girl's name), participants fail to develop this alternative strategy if the incongruent word is also invisible (cf. Ansorge, Heumann, & Scharlau, 2002;Cheesman & Merikle, 1985;McCormick, 1997). It is exactly this kind of reactive and changing rather than advance and fix top-down control that would also be necessary to control the processing of the next visual stimulus after a conflict-eliciting visual stimulus in a just preceding trial.…”
Section: Discussionmentioning
confidence: 99%
“…Ivanoff and Klein (2003) observed that after initial capture by invisible stimuli, attention could not be deallocated from the position of the capturing stimulus within 300 msec (see also Bauer, Cheadle, Parton, Müller, & Usher, 2009). Likewise, Ansorge et al (2002) found that the pace of learning to deallocate attention from an irrelevant singleton was proportional to the singleton's visibility. Thus, if the masked singleton priming effect did not depend on visibility, we expected a priming effect from masked, but not unmasked, prime singletons.…”
Section: Methodsmentioning
confidence: 96%
“…If there Dixon, 1970;Forster, 1998). The reason is that reactive modification of processing following a misguiding visual prime would be much harder with invisible than with visible stimuli (see Ansorge, Heumann, & Scharlau, 2002;Cheesman & Merikle, 1985). Ivanoff and Klein (2003) observed that after initial capture by invisible stimuli, attention could not be deallocated from the position of the capturing stimulus within 300 msec (see also Bauer, Cheadle, Parton, Müller, & Usher, 2009).…”
Section: Methodsmentioning
confidence: 99%